Internal Factors Affecting the Performance of Accounting Information Systems at the People’s Credit Bank (Study in Abiansemal Bali) - Putu Kepramareni; Sagung Oka Pradnyawati; Ni Putu Sri Savitri (AIBPM Publisher, 2022)
The Performance of the accounting information system is the result of processing the information system used by the user as well as the appraiser and evaluation of the implementation of the accounting information system used, by a company especially banking, in achieving the companyâ€™s goals. The performance of the accounting information system can be measured internally with indicators satisfaction with the use of the system and the use of the system itself. This study uses internal factors in the accounting information system to analyze their effect on the resulting performance. The study was conducted in the rural banking sector in Abiansemal Bali and obtained a sample of 40 by purposive sampling. The researcher is a non-participant observation and analyzes the data obtained using multiple linear regression.Â Keywords: Accounting Information System Performance, Information System Development Formalization, Internal Control System, Organization Size, Personal Engineering Ability